Health transformation toward universal healthcare coverage amidst conflict: examining the impact of international cooperation in Niger - Doutchi, Mahamadou; Ghousmane, Abdoulaye; Zampaligre, Fatimata; Moussa, Bizo; Ishagh, El Khalef; Talatou Marc, Ouédraogo; Oumarou, Batouré; Kaya, Mutenda Sheria; Diawara, Gbaguidi Aichatou; Camara, Abdoulaye Macire; Moussa, Seyni; Bienvenu, Kuyangisa; et al. (Frontiers in Public Health, 2024)
Background: Approximately 70% of Sub-Saharan African countries have experienced armed conflicts with significant battle-related fatalities in the past two decades. Niger has witnessed a substantial rise in conflict-affected populations in recent years. In response, international cooperation has aimed to support health transformation in Niger's conflict zones and other conflict-affected areas in Sub-Saharan Africa. This study seeks to review available evidence on health interventions facilitated by international cooperation in conflict zones, with a focus on Niger.We conducted a systematic literature review (SLR) adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search was conducted from 2000 to September 4, 2022, using mesh terms and keywords to identify relevant studies and reports in Sub-Saharan Africa and specifically in Niger. Databases such as PubMed (Medline), Google Scholar, Google, and gray literature were utilized. The findings were presented both narratively and through tables and a conceptual framework.Results: Overall, 24 records (10 studies and 14 reports) that highlighted the significant role of international cooperation in promoting health transformation in conflict zones across Sub-Saharan Africa, including Niger were identified. Major multilateral donors identified were the World Health Organization (WHO), United Nations Children's Fund (UNICEF), United Nations Fund for Population Activities (UNFPA), World Bank, United States Agency for International Development (USAID), European Union, European Commission Humanitarian Aid (ECHO), Global Fund, and Global Alliance for Vaccines and Immunization (GAVI). Most supports targeted maternal, newborn, child, adolescent, and youth health, nutrition, and psycho-social services. Further, interventions were in form of public health initiatives, mobile clinic implementation, data management, human resource capacity building, health information systems, health logistics, and research funding in conflict zones.This literature review underscores the significant engagement of international cooperation in strengthening and transforming health services in conflict-affected areas across Sub-Saharan Africa, with a particular focus on Niger. However, to optimize the effectiveness of health care activities in short-and long-term perspectives, international partners and the Ministry of Public Health need to re-evaluate and reshape their approach to health intervention in conflict zones.